Anatomical Localization of Traumatic Brain Injury Cases in Eastern Macedonia and Thrace, Greece: a 10-year Retrospective Observational Study - Karakasi, Maria-Valeria (Korean J Neurotrauma, 2020)
OBJECTIVE: Brain trauma is an extremely important economical and social issue with increasing daily incidence. It is important to observe and report brain trauma, in order to provide better conditions for improvement of the trauma prevention and management. METHODS: A ten-year retrospective observational analysis was performed on 292 (fatal and non-fatal) incidents of traumatic brain injury among 2,847 totally examined cases in the records of the laboratory of forensic sciences at Democritus University of Thrace between January 1, 2007 and December 31, 2016. The results were further analyzed and classified into pertinent categories associated with the purpose of the study. RESULTS: The average age was estimated at 47.24 years with an obvious male domination. The most common cause of TBI, according to the results, is transport accidents (61.85%) followed by trauma inflicted by blunt instrument (22.49%), fall from height (11.65%) and occupational accidents (4.02%). Mortality rates were evaluated for each type, revealing extremely disturbing numbers. Regarding the anatomical localization on the skull, the most common region of cranial fractures is the cranial base (16.48%), followed by the frontal (12.87%), occipital (11.29%) and parietal bones (11.06%). In the majority of the cases, there were associated injuries. CONCLUSION: The management of traumatic brain injuries is difficult and sometimes impossible. Better prevention measures are required to minimize as much as possible the incidence of brain trauma.